DPSK Signal Regeneration Using a Nonlinear Amplifying Loop Mirror - Sponsel, Klaus; Stephan, Christian; Cvecek, Kristian; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Conf. Proc. OFC, Paper OThB2, March, 2007)
Power characteristics and phase functions of a NALM are investigated in simulations and experimentally, showing a phase-preserving nonlinear characteristics suitable for amplitude regeneration of phase-encoded signals. A negative power penalty of -1.5 dB was obtained. ©2006 Optical Society of America.
UnivIS-Import:2017-12-18:Pub.2007.tech.IE.LEH.dpsksi